Reducing the Sodium Chloride Content in Chicken Pate by Using Potassium and Ammonium Chloride. (2015) - Lazic, Ivana Brankovic; Raseta, Mladen; Nikolic, Dragica; Lukic, Mirjana; Karan, Dragica; Lilic, Slobodan
Abstract: The aim of this research was to investigate possibility of chicken pate production with reduced sodium chloride content, as well as to establish changes in sensory characteristics. In the study, six experimental groups of chicken pate were produced with the same basic ingredients, but different amounts of added salts. Sensory evaluation was performed in order to determine general taste acceptability, and of the sodium and potassium levels in the chicken pate. The pate from EI and EII groups in which the amount of added sodium chloride was reduced and/or partially substituted with ammonium chloride had a most acceptable taste.